LEGAL PROTECTION COPYRIGHT OF BULDING OF CULTURAL HERITAGE ARCHITECTURE (CASE STUDY OF ARCHITECTURAL ARCHITECTURE BUILDING IN CITY OF BOGOR) - Nurwati SH., MH.; Jacobus Jopie Gilalo (JURNAL HUKUM DE'RECHTSSTAAT, 2017)
The change / delineation of buildings of cultural heritage architecture in Bogor City is not based on technical consideration, more on benefits and economics, and it is not in accordance / contrary to the provisions of Copyright Act No. 28 of 2014 on architectural works only allowed technical considerations. As the factor causing the nuance of the copyrighted works of cultural heritage architecture that many of the cultural heritage buildings that have moved from the first owner so that many in the total fox architecture of cultural heritage buildings that are also less effective legislation that brings people aware, because less socialization of legislation, the implementation of relatively light sanctions, lack of attention of local government in conservation efforts to the works of cultural heritage architecture. Due to the considerable cost. Efforts made to overcome the changes to the cultural heritage architectural work is to conduct good cooperation and coordination between institutions and related apparatus, to re-register and register in order to have the law, to give more severe sanction and firm, empower the buildings for example by way of functionalizing the building , increasing the role of architecture. This research is applicable law against culture heritage culture in Bogor city not yet implemented by law of Cultural Heritage and Copyright Act.